Two new species and additional records of the genus Geostiba Thomson, 1858 (Coleoptera: Staphylinidae: Aleocharinae) from Turkey - Örgel Semi̇h (Zootaxa, 2022)
In this study, two new species are described from Anatolia, Turkey and illustrated: Geostiba (Tropogastrosipalia) yamani sp. n. (Tokat province) and G. (T.) sinananlasi sp. n. (Sivas province). These two new species are compared to closely related species, G. priva Assing and G. solodovnikovi Assing. The distribution of these species is mapped, and an identification key of these species is provided. Additional records for six species are presented.